ANALISIS YURIDIS TENTANG KEDUDUKAN PRINSIP TANGGUNG JAWAB MUTLAK (ABSOLUT OF LIABILITY) DALAM PENYELENGGARAAN PENGANGKUTAN BARANG DENGAN KAPAL LAUT DI INDONESIA - RIDWAN LABATJO (Fakultas Hukum Universitas Muhammadiyah Luwuk, 2019)
The responsibility of carrier in the carriage of law is a form of protection in the process of hauling freight in the Treaty with the intention that the goods arrive at the places the destination safely and on time. But in the process of hauling, not closing the possibility there are things – things happen so that goods are not happy that is the goods suffered damage, lost, deficient, destroyed. So then there must be a responsible party. In studies of haulage by sea ships internationally recognize the principle of absolute liability (absolute of liability). In this paper the author will discuss with regards to puts the principle of absolute liability (absolute of liability) and the position of the ruling against regulation perudang – invitation of haulage with a ship in Indonesia, by using the methods of normative research i.e. research libraries (library research) by tracing the source of primary and secondary legal materials. Based on the research results then puts the principle of Absolute Liability (Absolute of Liability) asserts that the carrier be liable for any losses incurred due to any events in organizing transport without the necessity whether or not there is proof of the carrier's fault. The legal position of the principle of Absolute Liability (Absolute Of Liability) against regulation perudang – invitation haulage by sea ships in Indonesia, namely the principle of absolute liability (Absolute of Liability) in fact contradicts the book of law commercial law (KUHD) and section 101 of the Act Number 17-year 2008 about Cruise empirically that the carrier was not given the huge risk considering the sea transport companies in Indonesia still belongs to the small and medium sized businesses.